2012
DOI: 10.4209/aaqr.2011.08.0122
|View full text |Cite
|
Sign up to set email alerts
|

Emission reductions of Air Pollutants from a Heavy-duty Diesel Engine Mixed with Various Amounts of H2/O2

Abstract: This study investigated emission reductions of polycyclic aromatic hydrocarbons (PAHs), hydrocarbons (HCs), carbon monoxide (CO), carbon dioxide (CO 2 ), particulate matters (PM), and nitrogen oxides (NO x ) from a heavy-duty diesel engine (HDDE) at one low load steady-state condition, 24.5% of the maximum load (40 km/h), using premium diesel fuel (PDF) mixed with various amounts of H 2 /O 2 . Measurements showed that the mixed fuel of HO60 reduced the brake specific fuel consumption (BSFC) most, by an amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…formaldehyde), polycyclic aromatic hydrocarbons (PAHs), and nitro-PAHs (Chen et al, 2001;Grosjean et al, 2001;Mi et al, 2001;Lin et al, 2005;Ho et al, 2007;Legreid et al, 2007;BanWeiss et al, 2008;Chien et al, 2009;Lin et al, 2009;Shi et al, 2009;Shi et al, 2010;Srivastava et al, 2011;Yao et al, 2011;Wang et al, 2012). Therefore, alternative fuel is needed in the future.…”
Section: Introductionmentioning
confidence: 99%
“…formaldehyde), polycyclic aromatic hydrocarbons (PAHs), and nitro-PAHs (Chen et al, 2001;Grosjean et al, 2001;Mi et al, 2001;Lin et al, 2005;Ho et al, 2007;Legreid et al, 2007;BanWeiss et al, 2008;Chien et al, 2009;Lin et al, 2009;Shi et al, 2009;Shi et al, 2010;Srivastava et al, 2011;Yao et al, 2011;Wang et al, 2012). Therefore, alternative fuel is needed in the future.…”
Section: Introductionmentioning
confidence: 99%
“…As compared with the SI engine, it is close to zero. It could be explained that the principal source of NO x is the oxidation of nitrogen, which is temperature and oxygen concentration dependent (Wang et al, 2012). The combustion temperature of the HCCI engine is low.…”
Section: Hcci Operating Performancementioning
confidence: 99%
“…However, vehicles remain a major source of nitrogen oxides (NO x ), carbon monoxide (CO), hydrocarbons (HC), particulate matter (PM) and polycyclic aromatic hydrocarbon (PAH) emissions, and many researchers have suggested that mobile sources are the major contributor in urban and suburban environments (Lin et al, 2006a, b, c;Tsai et al, 2010a, b;Wu et al, 2010;Hsieh et al, 2011a, b;Karavalakis et al, 2011;Kim et al, 2011;Li et al, 2011;Shen et al, 2011;Srivastava et al, 2011;Yao et al, 2011;Cheng et al, 2012a, b;Lai et al, 2012;Liang et al, 2012;Liu et al, 2012;Pilusa et al, 2012;Tsai et al, 2012;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%